Abordagens freqüentista e bayesiana para avaliação genética de bovinos da raça Canchim para características de crescimento - Buranelo Toral, Fabio Luiz; de Alencar, Mauricio Mello; de Freitas, Alfredo Ribeiro (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2007)
This study aimed to: a) to compare the covariance components obtained by Restricted Maximum Likelihood (REML) and by bayesian inference (BI): b) to run genetic evaluations for weights of Canchim cattle measured at weaning (W240) and at eighteen months of age (W550), adjusted or not to 240 and 550 days of age, respectively, using the mixed model methodology with covariance components obtained by REML or by BI; and c) to compare selection decisions from genetic evaluations using observed or adjusted weights and by REML or BI. Covariance components, heritabilities and genetic correlation for W240 and W550 were estimated and the predicted breeding values were used to select 10% and 50% of the best bulls and cows, respectively. The covariance components obtained by REML were smaller than the a posteriori means obtained by Bl. Selected animals from both procedures were not the same, probably because the covariance components and genetic parameters were different. The inclusion of age of animal at weighing as a covariate in the statistical model fitted by BI did not change the selected bulls and cows.
Frequentist and bayesian approachs for genetic evaluation of Canchim beef cattle for growth traits
Keywords: a posteriori mean; Gibbs sampler; high-density interval; selection